Investigation of operation conditions of containers made in the form of long tubes - Джус, Андрій Петрович; Сусак, Олександр Михайлович (Eastern-European Journal of Enterprise Technologies, 2014)
Taking into account the technological features inherent in compressed natural gas transportation it was found that filling containers can be carried out using compressors during the whole process, and by introducing them at some stage. The possibility of different filling process duration was also noted. According to research results, it was found that for the two-stage filling conditions, temperature on the first three linear sections is characterized by particular nonuniformity. Introduction of the compressor leads to a rapid increase in gas temperature on the first, and later, on the second linear section. The temperature difference in the middle of these sections is 12°C. The nature of the nonuniformity at different process implementation rates is almost the same. For the container filling conditions with regular compressor use, temperature processes are characterized by especially pronounced nonuniformity in the early stages. The maximum temperature difference in the middle of adjacent sections is up to 6°C. With the increase in gas pressure, temperature processes are partially stabilized. For a deeper analysis of existing processes and their influence on the stress-strain state of long tube elements, further studies of the gas temperature change, in particular when unloading ships are necessary.